Psychosurgery: Review of Latest Concepts and Applications - Aydin, Sabri; Abuzayed, Bashar (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2013)
Although the utilization of psychosurgery has commenced in early 19th century, when compared with other neurosurgical fields, it faced many obstacles resulting in the delay of advancement of this type of surgical methodology. This was due to the insufficient knowledge of both neural networks of the brain and the pathophysiology of psychiatric diseases. The aggressive surgical treatment modalities with high mortality and morbidity rates, the controversial ethical concerns, and the introduction of antipsychotic drugs were also among those obstacles. With the recent advancements in the field of neuroscience more accurate knowledge was gained in this field offering new ideas for the management of these diseases. Also, the recent technological developments aided the surgeons to define more sophisticated and minimally invasive techniques during the surgical procedures. Maybe the most important factor in the rerising of psychosurgery is the assemblage of the experts, clinicians, and researchers in various fields of neurosciences implementing a multidisciplinary approach. In this article, the authors aim to review the latest concepts of the pathophysiology and the recent advancements of the surgical treatment of psychiatric diseases from a neurosurgical point of view.
Keywords: deep brain stimulation; neural networks; neuromodulation; psychiatric disorders; psychosurgery